The Relationship Between Parenting Styles, Self-Esteem and Peer Support on Anxiety in Grade XI Students of SMAN 5 Mataram - Widyasari, Ni Luh Rani; Adiwibawa, Danang Nur; Sherliyanah, Sherliyanah; Nirmala, Suci (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Individuals with high self esteem tend to be more confident and are therefore more capable of effectively coping with various situations, which ultimately reduces the likelihood of social anxiety. Peer support represents a form of affection from peers in the form of attention, assistance, and appreciation, providing both physical and psychological comfort through social interaction. This study aims to determine the relationship between parenting styles, self-esteem, and peer support on anxiety in 11th-grade students at SMAN 5 Mataram. This research utilized an observational analytical design with a cross-sectional method. The sample for this study included 92 students who were chosen through total random sampling. Data was gathered by using questionnaires to assess parenting styles, self-esteem, peer support, and anxiety levels. The analysis of the data was carried out with univariate and bivariate techniques employing the Spearman rank sum test. The findings indicated a notable correlation between authoritarian parenting styles and anxiety among 11th-grade students at SMAN 5 Mataram, with a p-value of 0.049 (p-value <0.05), signifying that Ho was rejected. There is a connection between self-esteem and anxiety in class XI students of SMAN 5 Mataram with a p-value of 0.005 (p-value <0.05), indicating that Ho is rejected. Additionally, there is a link between peer support and anxiety among class XI students of SMAN 5 Mataram with a p-value of 0.000 (p-value <0.05), which also means Ho is rejected. In summary, it can be concluded that there is an association between parenting styles and anxiety, a connection between self-esteem and anxiety, and a relationship between peer support and anxiety.